Dukungan Sosial Dengan Fear of Failure Pada Foodpreneur - Yugi Murdafasmi; Risana Rachmatan; Haiyun Nisa; Irin Riamanda (IJIP : Indonesian Journal of Islamic Psychology, 2020)
Abstract Social support is an exchange of resources between two individuals that are felt byboth the giver and the recipient with the aim of improving the welfare of the recipient. The social support received by entrepreneurs will certainly affect the smooth running of the business being run. One of the biggest fears that are owned by entrepreneurs, especially foodpreneurs, is fear of failure. The research objective was to determine the relationship between social support and fear of failure in foodpreneurs. The measuring instruments used in this study were the Multidimensional Scale Of Perceived Social Support (α = 0.81) and The Performance Failure Appraisal Inventory (α = 0.87). The sample was obtained by using quota sampling technique with the criteria of entrepreneurs in the culinary field aged 18-34 years, having their own culinary business with a total sample of 342 people. The analysis results showed that there was a negative relationship between social support and fear of failure in foodpreneurs. So the higher the social support, the lower the fear of failure. Likewise, on the other hand, the lower the social support, the higher the fear of failure. AbstrakDukungan sosial merupakan pertukaran sumber daya antara dua individu yangdirasakan oleh pemberi maupun penerima dengan tujuan meningkatkan  kesejahteraan bagi penerima. Dukungan sosial yang diterima oleh para pengusaha tentunya akan memengaruhi kelancaran dari usaha yang dijalankan. Salah satu ketakutan terbesar yang dimiliki oleh pengusaha terutama foodpreneur yaitu ketakutan akan kegagalan atau fear of failure. Tujuan penelitian adalah untuk mengetahui hubungan antara dukungan sosial dengan fear of failure pada foodpreneur. Alat ukur yang digunakan penelitian ini adalah Multidimensional Scale Of Perceived Social Support (α=0,81) dan The Performance Failure Appraisal Inventory (α=0,87). Perolehan sampel dilakukan dengan teknik quota sampling dengan kriteria pengusaha dalam bidang kuliner yang berumur 18-34 tahun, memiliki usaha kuliner sendiri dengan total sampel sebanyak 342 orang. Hasil analisa menunjukkan ada hubungan negatif antara dukungan sosial dengan fear of failure pada foodpreneur. Jadi semakin tinggi dukungan sosial maka semakin rendah fear of failure. Begitu juga sebaliknya bahwa semakin rendah dukungan sosial maka semakin tinggi fear of failure.